2017
DOI: 10.1177/2167702617719946
|View full text |Cite
|
Sign up to set email alerts
|

Mental Defeat and Cumulative Trauma Experiences Predict Trauma-Related Psychopathology: Evidence From a Postconflict Population in Northern Uganda

Abstract: The peritraumatic cognitive process of mental defeat, the complete loss of inner resistance, has been identified as a key predictor of PTSD. Yet, most evidence on cognitive risk factors stems from industrialized countries where survivors typically report few traumata. Research from postconflict settings indicates that individual differences decrease with accumulating traumatic experiences, as almost everybody develops PTSD at extreme levels of trauma load. Would this leave less room for the impact of cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Indeed, research has consistently suggested that the likelihood of suffering from posttraumatic stress increases when an individual is exposed to more of these stressors (Johnson & Thompson, 2008). For example, a robust dose–effect relationship has been found in multiple refugee and conflict‐affected populations, wherein cumulative exposure to more trauma has been shown to be associated with higher levels of posttraumatic stress (Mollica et al., 1998; Neuner et al., 2004; Wilker et al., 2017). Furthermore, certain experiences seem to confer an additional risk for poor mental health outcomes, particularly traumatic events that are interpersonal in nature, such as torture or sexual violence (Steel et al., 2009).…”
Section: External Factors Impacting Refugee Mental Healthmentioning
confidence: 99%
“…Indeed, research has consistently suggested that the likelihood of suffering from posttraumatic stress increases when an individual is exposed to more of these stressors (Johnson & Thompson, 2008). For example, a robust dose–effect relationship has been found in multiple refugee and conflict‐affected populations, wherein cumulative exposure to more trauma has been shown to be associated with higher levels of posttraumatic stress (Mollica et al., 1998; Neuner et al., 2004; Wilker et al., 2017). Furthermore, certain experiences seem to confer an additional risk for poor mental health outcomes, particularly traumatic events that are interpersonal in nature, such as torture or sexual violence (Steel et al., 2009).…”
Section: External Factors Impacting Refugee Mental Healthmentioning
confidence: 99%
“…Use of cognitive words in trauma narratives might reflect this elaboration process (15, 16). Peritraumatic mental defeat, a peritraumatic process, consisting of complete loss of inner resistance has also been implicated in the development in PTSD (14, 17, 18) as well as perceived threat to life (19). Earlier studies have indexed the use of death-related words in trauma narratives as linguistic indicator and proxy of these processes, which was related to PTSD as expected (20, 21).…”
Section: Early Linguistic Markers Of Trauma-specific Processing Predimentioning
confidence: 99%
“…Mental defeat has been found to predict PTSD symptom trajectories in prospective studies up to 6 to 9 months following trauma (Dunmore et al, 2001;Freeman et al, 2013;Kleim, Ehlers, & Glucksman, 2012). Studies to date have mostly focused on assault survivors (Dunmore et al, 1999(Dunmore et al, , 2001), survivors of political imprisonment (Ehlers, Maercker, & Boos, 2000), and on post-conflict contexts (Wilker et al, 2017).…”
mentioning
confidence: 99%